Collaborative-Constructivism Approach Reading Remediation - Osias Kit T. Kilag; Ma. Teresa B. Aniel; Viquelyn A. Engbino; Ana Lorraine B. Bubuli; Maridel D. Macapobre; Joana Marie L. Fajardo (CV. Ridwan Publisher, 2023)
The study focused on the students' reading challenges, the techniques, methods, and strategies used, as well as the changes seen following the mentoring sessions. The study's output was the formulation of a plan for peer mentoring. On the second grade non-readers in Toledo City's division, a study was done. The cases consisted of eight students. They all came from low-income homes, and three of them were Pantawid Pampamilyang Pilipino (4Ps) participants. The study was qualitative in character and using the multiple case study methodology. Employed Approaches, Methods, and Strategies Constructivist approaches were applied. Think, Pair and Read, find the underpinning, and Mix Mine were the collaborative learning tactics employed. Adjacent elementary schools in the district or in other districts should be made aware of the proposed peer mentoring plan. The following subjects are suggested for additional research: Developing Teachers' Creativity in the Mentoring Program Coaching and Mentoring as Realistic Ways to Enhance Learning. A management intervention program called mentoring.